Pengaruh Prinsip Character, Capacity, Capital, Collateral, Condition Of Economy Terhadap Pengambilan Keputusan Kredit PT. Bank Negara Indonesia KCU Cibinong Tahun 2020 - Ependi Ependi; Muhammad Awwabin (Ilmu Ekonomi Manajemen dan Akuntansi, 2020)
Bank Is A Financial Intermediary Institution Generally Established With The Authority To Manage Money Deposits. In Giving Credit There Are Several Things That Are Associated With Good Faith (Willingness To Pay) And Ability To Pay (Ability To Pay). Having the Problem Formulation Above Analyzing the Influence of These Factors is Very Important, namely "The Influence of Principles (Character, Capacity, Capital, Collateral, and Condition Of Economy) on Credit Decision Making at Pt. Bank Negara Indonesia Kcu Cibinong Year 2020", the theoretical basis used is the Theory of Credit Elements, Credit Provision Procedures, Identification, Legalization and Credit Realization Stages. This Research Uses Quantitative Methods With Results Showing That Character, Capacity, Capital, Collateral, Condition Of Economy Has A Significant Coefficient Of 0.000 0.005 And Fcount 27.041 Ftable 3.33 It Can Be Concluded That Ha Stating With Character, Capacity, Capital, Collateral , And The Condition Of Economy Simultaneously Significantly Affects Credit Decision Making. The Principle of Character, Capacity, Capital, Collateral, Condition Of Economy Has No Significant Influence on Credit Decision Making. And Simultaneously Character, Capacity, Capital, Collateral, Condition Of Economy Significantly Affect Credit Decision Making.Keywords: Character, Capacity, Capital, Collateral, Condition Of Economy, Credit Decision.